Comparison of intravenous infusion versus bolus dose of oxytocin in elective caesarean delivery: A prospective, randomised study - Jigisha P Badheka; Vrinda P Oza; Nitin S Manat; Mayur B Patel (Wolters Kluwer Medknow Publications, 2022)
Background: Oxytocin (OT) is routinely administered during caesarean delivery to prevent and treat postpartum haemorrhage (PPH). The common adverse effects of intravenous OT are tachycardia, hypotension, chest pain, Electrocardiogram (ECG) changes, nausea and vomiting. We aimed to compare the uterine contractility, haemodynamic changes, need for other uterotonics and adverse effects by comparing the intravenous bolus dose versus infusion dose of OT while retaining its benefits. Methods: Sixty patients undergoing elective caesarean delivery under spinal anaesthesia were randomised to receive OT 3 IU as a bolus (repeat 3 IU at an interval of 3 min) in group B (Bolus) or as an infusion 1 IU per minute in group I (infusion). The uterine tone was assessed by a blinded obstetrician as either adequate or inadequate. The intraoperative heart rate, blood pressure, blood loss and any other adverse events were recorded. Results: The adequacy of uterine tone was more sustained and the requirement of other uterotonics was less in group I. The heart rate increased to 20-25 beats/min at 3-5 min in group B and 8-10 beats/min at 2-4 mins and reached the baseline at 8-9 min in group B as well as in group I. Also, a significant fall in the mean blood pressure was observed at 3-5 min in group B. The ECG changes (ST-T changes) were more common in group B compared to group I. There was no significant difference in the estimated blood loss between the two groups. Conclusion: The infusion dose of OT provides more haemodynamic stability, better uterine tone and fewer adverse effects compared to the bolus dose.